Differential effects of clarithromycin and azithromycin on delayed rectifier K+-channel currents in murine thymocytes. (June 2013) - Kazama, Itsuro; Maruyama, Yoshio
Abstract Context: Lymphocytes predominantly express delayed rectifier K+-channels (Kv1.3) in their plasma membranes, and the channels play crucial roles in the lymphocyte activation and proliferation. Since macrolide antibiotics, such as clarithromycin and azithromycin, exert immunomodulatory effects, they would affect the Kv1.3-channel currents in lymphocytes. Objective: This study determined the physiological involvement in the mechanisms of immunomodulation by these antibiotics. Materials and methods: Employing the standard patch-clamp whole-cell recording technique in murine thymocytes, we examined the effects of 30 and 100 µM clarithromycin and azithromycin on the Kv1.3-channel currents and the membrane capacitance. Results: Clarithromycin significantly suppressed the peak currents (30 µM, 178 ± 5.6 to 111 ± 2.0 pA/pF; 100 µM, 277 ± 4.4 to 89.6 ± 10 pA/pF) and the pulse-end currents (30 µM, 47.5 ± 2.2% to 15.5 ± 3.3%; 100 µM, 48.5 ± 1.4% to 15.8 ± 1.0%) of thymocyte Kv1.3-channels without significant effects on the membrane capacitance. In contrast, azithromycin did not affect the channel currents. However, it significantly decreased the membrane capacitance (30 µM, 4.68 ± 0.14 to 3.74 ± 0.13 pF; 100 µM, 4.47 ± 0.06 to 3.37 ± 0.08 pF), indicating its accumulation in the plasma membrane. Discussion and conclusion: This study demonstrated for the first time that clarithromycin exerts inhibitory effects on thymocyte Kv1.3-channel currents, while azithromycin decreases the membrane capacitance without affecting the channel currents. These differences in the effects of the macrolide antibiotics may reflect differences in the mechanisms of immunomodulation by which they control the production of cytokines.